Pakistan's Investment Climate : Laying the Foundation for Growth, Volume 2. Annexes - Manes, Eric (Washington, DC, 2013)
Pakistan has faced a seismic shift in its global and domestic economic landscape which until recently limited policy options to address investment climate concerns. External shocks, internal policy inaction and political turmoil placed the country in a precarious economic condition, calling on the authorities to take a hard look at the policy choices ahead. Macroeconomic instability resulting in inflation, exchange rate depreciation, and a rapid depletion in foreign reserves became acute in 2007-08, with the adjustment accompanied by a reduction in investment, export and output growth. The recent slowdown in global demand for world trade along with supply shocks from the domestic economy has exacerbated an already monumental challenge for Pakistani firms to prosper and policy makers to respond. As external market conditions and Pakistan's own stabilization program temper economic expectations, opportunities abound to lay the foundation for expansion. Given Pakistan's geopolitical positioning, growing labor participation rates, and improvements in the standard of living, significant poverty outcomes can be achieved through sustained economic growth. Even, in the short run, during periods of slower growth, banking system weakness, and corporate distress, Pakistan can take the opportunity to position itself for the inevitable global rebound. Concerted efforts now can improve firm level productivity, fluidity of markets for labor, capital and land, as well as goods, and therefore, better resource use and global competitiveness.